Partial Purification of Deamidase from Germinating Wheat (Triticum aestivum L.) Seeds and its Application for the Improvement of Functional Properties of Wheat Gluten - Rahman, ATM Mijanur; Sana, NK; Khan, Md Masudul Hasan; Sarkar, BC; Huque, EM; Kumar, Shaha Ranajit (Journal of Bio-Science, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Enzyme with deamidase activity was found in the germinating wheat seeds. The activity appeared in the seeds after 24 hours of germination and reached its maximum value after 48 hours and then declined rapidly. Protein deamidase from germinating wheat seeds was further purified by salting out with phosphate salts and by subsequent chromatography on gel filtration and DEAE-cellulose column chromatography. Polyacrylamide slab gel elec trophoresis showed the purified enzyme to be homogeneous. The molecular weight was determined to be 59 kDa by gel filtration and 60 kDa, by SDS-Polyacrylamide slab gel electrophoresis (SDS-PAGE). The optimum pH and temperature of the purified enzyme were found to be 6.9 and 32°C, respectively.The functional properties of wheat gluten were investigated after treating with it purified deamidase enzyme from germinating wheat seeds at pH 6.9 at 32°C. The functional properties such as solubility, emulsification and foam formation of deamidase treated gluten were improved greatly as compared to that of native gluten. The solubility of the deamidase treated gluten was remarkably high in the pH range of 6 to 8, in which the native gluten was insoluble. It was apparent that the improvement of functional properties of wheat gluten was mainly due to the deamidation induced by wheat deamidase at pH 6.9 and 32°C. Key words: Wheat seeds, Deamidase, Deamidation, Wheat gluten, DEAE-cellulose, SDS-PAGE. DOI: http://dx.doi.org/10.3329/jbs.v15i0.2208 J. bio-sci. 15: 89-98, 2007